The Dictator and his Town: Aspects in the Planning and Development of Tikrit under Saddam Hussein - Zeidel, Ronen (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2005)
Town planning often involves the transformation of politics into the visual sphere. This is especially true in dictatorships such as Baathist Iraq, where the dictator is strongly engaged in planning. In most cases the dictatorial regime either chooses an already established urban center to become his showcase or constructs a brand new center, in which his architectural vision can be fully expressed. The Iraqi case is somewhat different, since the Baathist regime developed two showcases: Baghdad and Tiqrit. While the choice of Baghdad seems natural, the choice of Tiqrit requires some explanation. The transformation of Tiqrit — an off-the tourist-track provincial town lacking major attractions — into a secondary showcase can only be understood in the light of Saddam’s personality cult and his intricate relationship with his townsmen.